The effect of hypericum drop in restless legs syndrome in hemodialysis patients referred to selected hospitals in Tehran in 2016 - Nasrollah, Sepideh; Safavi, Mahboubeh; Mahmoudi, Mahmoud; Salehi Surmaqi, Mohammad Hossein (Advances in Nursing & Midwifery, 2017)
Abstract Background and Aim: Restless Legs Syndrome is one of the symptoms of chronic renal insufficiency. It is described as the discomfort and vague feelings in the patient’s legs. There is no drug to treat restless legs syndrome, but in traditional medicine, Hypericum Perforatum has been recommended. Hypiran drop from the plant is provided. The aim of this study was to determine the effects of hypericum drop on restless legs syndrome in hemodialysis patients referred to selected hospitals of Tehran. Materials and Methods: This was a clinical trial. 180 dialyses patients referred to hospitals in Tehran participated. The samples were randomly allocated into the two groups. The patients in intervention and control groups received hypericum drop and placebo respectively. Data was gathered by questionnaire (questions related to demographic information and questions related to diagnostic criteria and severity of restless legs syndrome). The data was analyzed using Mantel-Haenszel Test. Findings: The results showed that most of the subjects had severe restless legs syndrome, but after the intervention, the severity was reduced to moderate. The difference was statistically significant. In the control group, the severity of restless leg syndrome did not change between two measurements. As a result, there was a significant difference between the two groups. Conclusion: According to the results, it is necessary that dialysis ward’s nurses pay more attention to this problem and in providing information and education to patients with this syndrome. Keywords: Restless Legs Syndrome; Hypericum; Dialysis